(untitled) (International Current Pharmaceutical Journal, 2015)
Paracetamol is a widely used analgesic and antipyretic drug worldwide. The present study was conducted to analyze the quality of seven marketed brands of paracetamol tablet formulation manufactured by different multinational and national companies. The tablet formulations of different brands were tested for various parameters like weight variation, hardness, friability, disintegration time and dissolution profile using standard techniques to evaluate their quality. The values were compared with the standards. Weight variation value requirement was complied by all brands. All studied samples except two local products complied with the standard specification for tablet hardness. All brands showed impressive friability values and products of multinational companies comparatively exhibited the highest values. Disintegration time for all brands was within 15 minutes also complying the USP (United State of Pharmacopeia) recommendation. Moreover, the release rate of different brands of paracetamol was satisfactory within 45 minutes and ranged from 79.82% to 103.53%. Therefore, it can be concluded that almost all the brands of paracetamol that are available in Bangladesh meet the USP specification for quality control analysis. Kar et al., International Current Pharmaceutical Journal, August 2015, 4(9): 432-435